Resilience and social skills in high school students of San Luis de Shuaro, La Merced - Sharon Stefany Sosa Palacios (2020)
The aim of this research was to study the relationship between resilience and social skills, involving 212 students from four secondary schools and state management, belonging to San Luis de Shuaro district, located in the central jungle of Perú; They study at different levels, from first to fifth grade of secondary school, their age range from 11 to 20 years, 52% are men. The instruments that were used were the Resilience Scale for Adolescents of Prado & Del Águila (2003) and the Goldstein Social Skills Check List, standardized by Tomás & Lescano (2003). It was found that resilience correlates positively with the dimensions of social skills, specifically high correlations were obtained with the dimensions: stress skills, communication skills, planning skills, alternative skills to violence and feelings-related skills. When comparing the results by sex, significant differences in planning skills were also found, with women scoring higher.